Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry